Convents confront the Reformation : Catholic and Protestant nuns in Germany - Wiesner-Hanks, Merry E., 1952- (Reformation texts with translation (1350-1650). Women of the Reformation, 1996)
This book is an outgrowth of the search for new sources which reveal the experience of women during the Reformation period. The four texts in this volume are all by women who resided in convents or similar institutions, or who had recently left convents, in Germany in the sixteenth and seventeenth centuries. They allow us to hear - with some filtering by their male editors and publishers - women's opinions about the merits of clerical celibacy and convent life. The first work is a letter of Katherine Rem of the Katherine convent in Augsburg to her brother Bernard - and an excerpt from his answer to her and to his daughter, who was also in the convent - printed in Augsburg in 1523. The second is a letter of Ursula of Munsterberg to her cousins Dukes George and Heinrich of Saxony, explaining why she left the convent of Mary Magdalene the Penitent in Freiberg, first printed in 1528 and later reprinted with an afterword by Luther. The third source is selections from a book of meditations, Der treue Seelenfreund Christus Jesus, written by the Lutheran abbess of Quedlinburg, Anna Sophia, the daughter of the Duke of Hesse, first published in Jena in 1658. The final source is a pamphlet written by Martha Elisabeth Zitter describing reasons for leaving the Ursuline convent in Erfurt, printed in Jena in 1678.